Recontextualizing the Swedish national preschool curriculum: local authorities’ formulation of preschool principals’ accountability for quality work - Sophia Rudeberg (Nordic Journal of Studies in Educational Policy)
This paper focuses on ideas of preschool principals’ responsibilities for quality work expressed in Swedish local authorities’ policy documents. Empirically, it is based on a three-step analysis of 202 policy documents from 21 Swedish local authorities. This involved thematic analysis followed by application of a discursive institutionalist lens and assessment of the alignment of policies and accountability structures expressed in the documents with national policies. The result of the analysis shows that the national preschool curriculum plays a role in shaping ideas about preschool principals’ responsibilities at the local level, notably the overarching idea of ‘equivalence’, emphasizing their responsibilities for promoting social and economic equality. However, the recontextualization of the national curriculum is also influenced by socio-economic conditions, such as limitations of staff and resources available to the local authorities, highlighting a need to tailor accountability in accordance with the local authorities’ contexts. This results in varying degrees of alignment and accountability, with expressions in the local authorities’ policy documents sometimes extending beyond national guidelines and offering inconsistent support for preschool principals. The paper also illustrates that preschool principals may struggle to take responsibility for quality work due to the emphasis on local contextual needs.